2021
DOI: 10.3389/fonc.2021.698773
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Application of 3D-Printed Boluses in Superficial Tumor Radiotherapy

Abstract: During the procedure of radiotherapy for superficial tumors, the key to treatment is to ensure that the skin surface receives an adequate radiation dose. However, due to the presence of the built-up effect of high-energy rays, equivalent tissue compensators (boluses) with appropriate thickness should be placed on the skin surface to increase the target radiation dose. Traditional boluses do not usually fit the skin perfectly. Wet gauze is variable in thickness day to day which results in air gaps between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The 3D-printed plastic plates enable the peak dose in the mini-beam dose profile. Thanks to the fast prototyping of the 3D-printing technology, [22][23][24] it was not only possible to create several plastic plates with different thicknesses and angles to change FWHM and ctc as well as compensate for beam divergence but also to design mounting setups for reproducible positioning of the mini-beam collimator in the MultiRad. The relevance of aligning the mini-beam collimator properly in the center of the X-ray radiation field is illustrated in Figure S7.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D-printed plastic plates enable the peak dose in the mini-beam dose profile. Thanks to the fast prototyping of the 3D-printing technology, [22][23][24] it was not only possible to create several plastic plates with different thicknesses and angles to change FWHM and ctc as well as compensate for beam divergence but also to design mounting setups for reproducible positioning of the mini-beam collimator in the MultiRad. The relevance of aligning the mini-beam collimator properly in the center of the X-ray radiation field is illustrated in Figure S7.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of the present study is that we did not use 3D printed boluses when conducting radiotherapy for patients with superficial electron beam. The research of Wang X et al shows that 3D printed boluses can reduce the air gap between skin surface and bolus, improve the accuracy and uniformity of radiation dose, better protect normal tissues, and have obvious advantages in cost and time efficiency (17). In the course of radiotherapy for such patients in the future, 3D printed boluses can be considered to achieve better therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have consequently demonstrated a reduction in the air gap and an improvement in the accuracy of the dose build-up, while also reducing the time and money required. However, there have been few reports of these boluses being employed in clinical practice, and past research has rarely considered the characteristics of repetition of RT sessions [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%